2017
DOI: 10.1002/cm.21391
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic balance between global repulsion and local attraction in reentrant polymerization of actin

Abstract: Actin polymerization depends on the salt concentration, exhibiting a reentrant behavior: the polymerization is promoted by increasing KCl concentration up to 100 mM, and then depressed by further increase above 100 mM. We here investigated the physical mechanism of this reentrant behavior by calculating the polymerization energy, defined by the electrostatic energy change upon binding of an actin subunit to a filament, using an implicit solvent model based on the Poisson-Boltzmann (PB) equation. We found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…As with the occupancy simulations of Fig. , studying the kinetics of the profilin‐actin transfer mechanism explicitly would require a detailed model of binding and polymerization . We take here a simpler approach by asking if either FH1 domain can reach out and with what probability to the polyproline binding pocket of profilin at the terminal actin subunit.…”
Section: Resultsmentioning
confidence: 99%
“…As with the occupancy simulations of Fig. , studying the kinetics of the profilin‐actin transfer mechanism explicitly would require a detailed model of binding and polymerization . We take here a simpler approach by asking if either FH1 domain can reach out and with what probability to the polyproline binding pocket of profilin at the terminal actin subunit.…”
Section: Resultsmentioning
confidence: 99%
“…The complex electrostatic interactions of the highly charged actin molecule may also contribute to this effect (39). It has been reported that the actin polymerization ∆H changes sign and ∆S decreases 60-fold as the KCl concentration increases from 30 to 100 mM (55), at which point the critical concentration exhibits a minimum (30). An important factor that we did not include, and which may play a role in enhancing long-pitch helix contacts, is the divalent cation binding at the "polymerization cation site" between subdomains 3 and 4 or at the "stiffness cation site" within the D-loop interface (39).…”
Section: Discussionmentioning
confidence: 99%
“…ecent studies focusing on interactions of charged proteins in electrolyte solutions have highlighted the interplay of two counteracting electrostatic forces (1)(2)(3)(4). The first one originates from the presence of a localized distribution of charges defining an electrostatic patch on the protein surface.…”
mentioning
confidence: 99%